A Vision for Gastrin-Releasing Peptide Receptor Targeting for Imaging and Therapy: Perspective from Academia and Industry - Morgat, Clément; Duan, Heying; Dalm, Simone; Hindié, Elif; Günther, Thomas; Krause, Bernd J; Kramer, Vasko; Cavelier, Florine; Stephens, Andrew W; Moran, Stephen; Lamb, Laura; Iagaru, Andrei (The Journal of nuclear medicine (1978), 2025)
The gastrin-releasing peptide receptor (GRPR) is overexpressed in various cancers, including prostate cancer, breast cancer, small cell and non-small cell lung cancer, uterine and ovarian cancer, colon cancer, and gastrointestinal stromal tumors. This makes GRPR a multicancer target for theranostics, that is, molecular imaging and therapy. Here, we explore the current state of GRPR-targeted theranostics from bench to bedside, highlighting the preclinical development of various GRPR-targeting compounds and clinical applications. We review the role of GRPR-targeted molecular imaging for all stages of prostate cancer, breast cancer, and other tumors and provide a quo vadis GRPR. We aimed to offer a comprehensive overview of GRPR-targeted theranostics to inform researchers, clinicians, pharma, and regulators of the potential benefits and emerging opportunities in the pursuit of personalized precision cancer care.